2018
DOI: 10.1016/j.biopha.2018.08.147
|View full text |Cite
|
Sign up to set email alerts
|

RIPK4 promoted the tumorigenicity of nasopharyngeal carcinoma cells

Abstract: RIPK4 (receptor interacting serine/threonine kinase 4) has been reported to be aberrantly expressed in several cancer types. However, its expression pattern and functions in nasopharyngeal carcinoma (NPC) have never been reported. In this study, we have shown that the expression of RIPK4 was up-regulated in NPC tissues. RIPK4 promoted the growth and anchorage-independent growth of NPC cells, and down-regulation of RIPK4 inhibited the growth of NPC cells both in the plate-based culture and on the soft agar. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…expression is upregulated in nasopharyngeal, pancreatic, bladder urothelial and cervical squamous cell carcinoma, and is associated with a poor outcome [30][31][32][33]. Increased SCNN1A contributed to unfavorite prognosis in pulmonary adenocarcinoma and ovarian cancer [34][35].…”
Section: Discussionmentioning
confidence: 99%
“…expression is upregulated in nasopharyngeal, pancreatic, bladder urothelial and cervical squamous cell carcinoma, and is associated with a poor outcome [30][31][32][33]. Increased SCNN1A contributed to unfavorite prognosis in pulmonary adenocarcinoma and ovarian cancer [34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Though interacting with the adaptor protein DVL2, RIPK4 could stimulate Wnt Signaling pathway with the co-receptor LRP6, which suggests that RIPK4 overexpression may contribute to the growth of OC [18]. Gong et al (2018) revealed that the expression of RIPK4 was up-regulated in nasopharyngeal carcinoma (NPC) tissues and it could promote the growth and anchorage-independent growth of NPC cells, which demonstrated the oncogenic roles of RIPK4 in NPC and suggested that RIPK4 might be a therapeutic target [19]. High expression of RIPK4 was also observed in bladder urothelial carcinoma tissues and was an independent predictor for poor overall survival [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that NF-κB signaling is, in part, regulated by RIPK4 [138] and that RIPK4 is involved in several oncogenic pathways, including RAF/MEK/ERK signaling and Wnt/beta-catenin signaling [139,140,141]. Multiple studies demonstrated that either up- [139,142] or down-regulation [143,144] of RIPK4 activity is associated with tumor progression and an unfavorable oncological outcome in several cancers.…”
Section: Hydroxylation Of Non-hif Targets Mediated By Factor-inhibmentioning
confidence: 99%